A novel and selective sodium‐glucose cotransporter‐2 inhibitor, tofogliflozin, improves glycaemic control and lowers body weight in patients with type 2 diabetes mellitus. Issue 10 (20th August 2015) - Ikeda, S.; Takano, Y.; Cynshi, O.; Tanaka, R.; Christ, A. D.; Boerlin, V.; Beyer, U.; Beck, A.; Ciorciaro, C.; Meyer, M.; Kadowaki, T.
<x xml:space="preserve">Abstract</x> Aim To assess the efficacy, safety and tolerability of different doses of tofogliflozin, a novel, highly selective sodium‐glucose cotransporter 2 (SGLT2) inhibitor, in patients with type 2 diabetes mellitus (T2DM). Methods In a 12‐week, multicentre, multinational, randomized, double‐blind, parallel‐group, placebo‐controlled, dose‐finding study, patients with inadequate glycaemic control from diet and exercise alone, or from diet and exercise plus a stable dose of metformin, were randomized to one of five doses of tofogliflozin (2.5, 5, 10, 20, or 40 mg) or placebo. The primary efficacy endpoint was absolute change at week 12 from baseline in glycated haemoglobin (HbA1c), minus the change in the placebo group. Results Statistically significant dose‐dependent reductions in HbA1c were shown in all treated groups except the 2.5‐mg dose group, with a maximum reduction of 0.56% (placebo‐subtracted) at the 40‐mg dose, along with increased urinary glucose excretion. Metformin treatment had no substantial influence on tofogliflozin efficacy. Dose‐dependent reductions in fasting plasma glucose and body weight were observed, and glucose intolerance was improved, with a trend towards blood pressure reduction. Slight increases were observed for mean ketone bodies with no abnormal change in ketone body ratio. No deaths or treatment‐related serious adverse events were reported. The incidence of adverse events was similar in the placebo (37.9%) to that in the tofogliflozin group (35.9–46.3%). Withdrawal because of adverse events was rare (≤2 patients per treatment group), with similar rates of withdrawal in the placebo and tofogliflozin groups. Conclusions A once‐daily dose of tofogliflozin for 12 weeks was an effective, safe and well‐tolerated treatment for T2DM.